Enhancing Community Welfare Through the Educational Forest Program: A Case Study in East Flores Regency, East Nusa Tenggara Province - Andino Chliston; Akerina; Deay Famas (IHSA Institute, 2024)
This research examines the impact of the Educational Forest Program on the welfare of forest edge communities in East Flores Regency, East Nusa Tenggara Province. Forest conservation and community welfare are intertwined aspects of sustainable development, particularly in regions where forests are vital resources for local livelihoods and environmental stability. Through a mixed-methods approach, incorporating quantitative surveys and qualitative interviews, the study assesses the program's effectiveness in fostering economic empowerment, environmental conservation, social cohesion, and community resilience. Findings reveal significant improvements in income levels, livelihood opportunities, and environmental conservation practices among program participants. Economic empowerment initiatives, such as alternative livelihood training and value-added enterprises, have led to increased household incomes and reduced dependency on forest resources. Environmental conservation efforts, including reforestation and sustainable land management, have enhanced forest cover and biodiversity. Moreover, the program has strengthened social cohesion and community resilience by promoting participatory decision-making processes and access to social services. Challenges remain, including limited funding and institutional support, but opportunities exist for enhancing the program's effectiveness and sustainability through strengthened community participation, integration of traditional knowledge, and multi-stakeholder collaboration. Overall, the Educational Forest Program represents a promising model for promoting the welfare of forest edge communities and supporting sustainable forest management in East Flores Regency and beyond.